2008
DOI: 10.1007/s10708-008-9239-4
|View full text |Cite
|
Sign up to set email alerts
|

The other side of civil society story: women, oil and the Niger Delta environmental struggle in Nigeria

Abstract: The study based on the outcome of a 2 year involvement with women organizations in the oil rich Niger Delta region of Nigeria avers that in spite of their apparent invisibility in the dominant Niger Delta discourse, women form the first line of social defence against socio-economic privation in the region. The women play active socio-economic roles in the hostile Niger Delta environment in engendering and sustaining group and individual development. In spite of the structural and cultural limitations imposed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Even though it has been adjudged that women have potentials that are necessary for national and global impact, Anugwom (2009) and Ezegbe and Akubue (2012) reported that women are still been denied basic rights. In general employment rights, Kumar (2013) reported that there exist direct or indirect discrimination against women workers.…”
Section: Women Participation In the Construction Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…Even though it has been adjudged that women have potentials that are necessary for national and global impact, Anugwom (2009) and Ezegbe and Akubue (2012) reported that women are still been denied basic rights. In general employment rights, Kumar (2013) reported that there exist direct or indirect discrimination against women workers.…”
Section: Women Participation In the Construction Industrymentioning
confidence: 99%
“…Hence, the tag of a very stressful industry. Anugwom (2009) observed that this has affected women physically and psychological, seeing themselves as inadequate and unsuitable workers, thereby leading to under-performance in the workplace. In addition, the male only image portrayed by the construction industry needs to be stopped.…”
Section: Sum Of Squaresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ibeanu (2005) stresses that women in the Niger Delta were central to abating militancy by negotiating new gender relations and reconciling the state with militants. Women mostly function there as peace brokers and custodians of order (Anugwom and Anugwom 2009). Women also exploit their social networks and gender-specific activities to mitigate the danger posed by militant youths (Anugwom 2011).…”
Section: Women's Inclusion In "Countering Violent Extremism" Activitiesmentioning
confidence: 99%
“…The importance of trust in monitoring and managing such risks demands that risk managers put forth serious effort into building and maintaining trustworthiness and credibility within the community. Anugwom and Anugwom (2009) suggested that to mitigate the adverse effects of mining activities in the Niger-Delta area of Nigeria, "intervention efforts should target women and their organizations as crucial modes of mediation in both socio-economic spheres and in the elusive peace building efforts in the region" (p. 334). They argue that women's groups play a critical role in the socio-economic development of the local communities and the region at large.…”
Section: Most Common Adverse Effectsmentioning
confidence: 99%